Um modelo matemático via sistema baseado em regras fuzzy para avaliação do processo ensino-aprendizagem - Lunetta, Camila (2023)
This work aims to propose a model/tool through a rule-based fuzzy system to assist the teacher in the complex task of evaluating student learning, aiming to consider subjective aspects inherent in the evaluation process. The major contribution of this tool is that the teacher will be able to choose which and how many forms of assessment to adopt to determine the student's final grade. The main advantage of the model is the ability to classify students' performance by considering the use of different criteria (input variables) for the composition of the final grade (output variable), using qualitative and quantitative information treated as fuzzy sets. Subsequently, we applied this model in a Mathematics class in the Middle School of a public school. For computational implementation of the model, the MATLAB software Toolbox Fuzzy and the Python programming language were used. We hope that the proposed model here becomes a new and useful tool to assist educators in determining students' performance throughout the academic year.